Assessing cultivar-specific susceptibility and morphological adaptations of Bactrocera oleae (Diptera: Tephritidae) in olive orchards - Pajac Zivkovic, Ivana; Cirjak, Dana; Hojsak, Luka; Vrcek, Barbara; Suazo, Manuel J.; Benitez, Hugo A.; Lemic, Darija (My University, 2025)
The olive fruit fly, Bactrocera oleae (Rossi), is the most important widespread pest in olive-growing areas worldwide, causing significant yield losses and deterioration of olive oil quality. This study hypothesized that olive cultivars differ in their susceptibility to B.oleae and that the cultivar in which the pest develops may affect population variability. The primary goal was to assess susceptibility across 6 olive cultivars, while the secondary goal was to analyze population variability using geometric morphometrics to identify cultivar-specific phenotypic differences. Conducted at 2 sites, Banjevci (Dalmatia) and Vodnjan (Istria), the study revealed significant differences in infestation levels, emergence, and wing morphology. Higher humidity in Vodnjan favored increased fly populations. Larger-fruited cultivars such as Oblica, Istarska bjelica, and Ascolana tenera experienced higher infestation rates, whereas smaller-fruited cultivars like Frantoio and Leccino exhibited lower infestation levels. Wing shape analysis highlighted sexual dimorphism, with female flies exhibiting broader wings that may enhance dispersal and oviposition efficiency, particularly in larger fruits. The observed phenotypic plasticity of B. oleae across cultivars and locations indicates an ability to adapt to varied host and cultivation conditions, enhancing pest resilience. The findings underscore the role of cultivar selection as a passive pest management strategy and demonstrate the utility of geometric morphometrics in capturing cultivar-specific morphological adaptations.
Keywords: tephritidae; cultivar susceptibility; geometric morphometrics; wing shape adaptation